A Cross-Sectional Study: The Relationship Between Knowledge and Attitudes of Doctors Regarding the Principle of Autonomy for Patients with Sexually Transmitted Infections - Taufan, Ali; Sari, Sylvia Mustika; Sari A, Devita (Chakra Brahmanda Lentera Institute, 2025)
Background: Ethical dilemmas in handling cases of Exclusively Transmitted Infections (STIs) are often experienced by doctors due to their knowledge and attitudes in respecting the patient's right to autonomy. The objective of the research is to study the practitioners’ knowledge and attitudes concerning autonomy principles in facing STI patients. Methods: This cross-sectional analytical study involved a total sampling of 32 general practitioners at Dustira Hospital. A researcher-designed, validated, and reliability-tested questionnaire was used to measure doctors’ knowledge (independent variable) and attitudes (dependent variable) toward patient autonomy. Expert consultation and a pilot test at Cibabat Hospital were conducted to ensure instrument suitability. Data were analyzed using the Pearson correlation test, and ethical approval was obtained before the study.. Results: The results showed that 66% of general practitioners at Dustira Hospital had good knowledge of the principle of autonomy in managing patients with sexually transmitted infections (STIs). Doctors with over five years of experience demonstrated better knowledge (73%) compared to those with less experience (58.2%). Interestingly, among less experienced doctors who frequently treated STI patients, all had poor knowledge, whereas those who treated STI patients less often showed better knowledge (63%). Regarding attitudes, 53% of respondents had a good attitude toward autonomy-related ethical dilemmas. A greater proportion of doctors with more than five years of experience (60%) had good attitudes than those with less experience (47%). Notably, less experienced doctors who frequently managed STI cases showed entirely poor attitudes. Pearson correlation analysis indicated no significant relationship between knowledge and attitude (p = 0.425), with a very weak negative correlation (r = –0.146). Conclusion: General practitioners with more work experience tend to demonstrate better knowledge and attitudes regarding patient autonomy in STI cases. However, practitioners with less than five years of experience who frequently treat STI patients exhibit both poor knowledge and unfavorable attitudes. A tendency toward empirical, experience-based decision-making over rational, principle-based reasoning may influence this.